Spirituality among parents of children with cancer in a Middle Eastern country - Doumit, Myrna A.A. (2019)
Purpose Family caregivers of children with cancer face emotional, psychological, and spiritual challenges coping with their child's illness. For ensuring comprehensive multidisciplinary pediatric care, there is a need to understand and define what spirituality means for them in relation to their child's illness. The purpose of this study is to understand the meaning of spirituality for parents of cancer patients in Lebanon. Methods This qualitative study followed the Heideggerian interpretive phenomenological method. Through purposeful sampling, 11 parents (mother or father) of children with cancer receiving treatment at a tertiary care center in Beirut, Lebanon were interviewed. Data were analyzed following the hermeneutical process as described by Diekelmann and Ironside (1998). Results A constitutive pattern and overarching theme, “spirituality is a two-level relationship. It is a relation with God and with people. It is the act of receiving and giving back” and five major themes emerged from the data. These were "Being there for me; " "Connectedness with other parents is a blessing and a torment; " "The power of knowing; " "Communication with Unknown" and "Spirituality is not religiosity". Conclusion Lebanese parents of children with cancer defined the elements of their own spirituality. Relational aspects dominated and communication was an important factor. Implications for practice: This is the first study in the Middle East to address the meaning of spirituality in this population, and would pave the way for a customized palliative care program and integrative approach to patient care.